PTPN14 acts as a candidate tumor suppressor in prostate cancer and inhibits cell proliferation and invasion through modulating LATS1/YAP signaling. (October 2020) - Wang, Rong; Du, Yonghao; Shang, Jin; Dang, Xiaomin; Niu, Gang
Abstract: Protein tyrosine phosphatase, non-receptor type 14 (PTPN14) exerts a profound effect in the progression of multiple malignant tumors. However, whether PTPN14 plays a role in prostate cancer has not been well investigated. Herein, we evaluated the function and potential underlying mechanism of PTPN14 in prostate cancer. Decreased PTPN14 expression was detected in prostate cancer, and restoration of PTPN14 expression in prostate cancer cells inhibited the proliferative and invasive potential. Mechanistically, PTPN14 increased the phosphorylation of Yes-associated protein (YAP) by activation of large tumor suppressor 1 (LATS1), an action that resulted in a significant reduction in YAP-mediated transcriptional activity. Inactivation of YAP by its inhibitor markedly abrogated the PTPN14-knockdown-induced promotion effect on prostate cancer cell proliferation and invasion. Notably, PTPN14 up-regulation also exerted a remarkable suppressive impact on tumorigenesis of prostate cancer in vivo . Taken together, the study reveals a tumor-inhibition role of PTPN14 that represses the proliferation and invasion of prostate cancer by down-regulating YAP activation. Highlights: PTPN14 expression is detected in prostate cancer. PTPN14 exerts tumor-suppressive function in prostate cancer. PTPN14 inhibits YAP activation via LATS1. PTPN14 regulates prostate cancer progression by YAP signaling.